2017
DOI: 10.1038/s41598-017-03801-x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Inhibits Arterial Calcification by Promoting Autophagy

Abstract: Arterial calcification is a major complication of cardiovascular disease. Oestrogen replacement therapy in postmenopausal women is associated with lower levels of coronary artery calcification, but its mechanism of action remains unclear. Here, we show that oestrogen inhibits the osteoblastic differentiation of vascular smooth muscle cells (VSMCs) in vitro and arterial calcification in vivo by promoting autophagy. Through electron microscopy, GFP–LC3 redistribution, and immunofluorescence analyses as well as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…Based on previous reports, modulating autophagy was investigated as a preventive strategy against VC. Likewise, representative autophagy inducers, such as rapamycin and valproic acid, have been shown to inhibit VSMC calcification in vitro [120,132]. However, since there is a possibility that pharmaceutical manipulation exhibits a nonspecific, off-target effect, it is necessary to study the therapeutic effect on calcification, as a method to determine autophagy-specific effects.…”
Section: Autophagy Inhibitionmentioning
confidence: 99%
“…Based on previous reports, modulating autophagy was investigated as a preventive strategy against VC. Likewise, representative autophagy inducers, such as rapamycin and valproic acid, have been shown to inhibit VSMC calcification in vitro [120,132]. However, since there is a possibility that pharmaceutical manipulation exhibits a nonspecific, off-target effect, it is necessary to study the therapeutic effect on calcification, as a method to determine autophagy-specific effects.…”
Section: Autophagy Inhibitionmentioning
confidence: 99%
“…According to the manufacturer's instructions, cell lysates were measured for alkaline phosphatase (ALP) activity using an ALP assay kit (A059-2, Jiancheng, Nanjing) and for osteocalcin secretion using an osteocalcin assay kit (H152, Jiancheng, Nanjing). As previously described, 15 ALP activity and osteocalcin secretion were normalized to the total cellular protein of the cellular layers, as determined by the Bradford protein assay. Results are presented as the fold-change compared with that of the control from three independent experiments.…”
Section: Calcification Assaysmentioning
confidence: 99%
“…Vascular calci cation is mainly characterized as the medial of aortic calci cation (termed as Mönckeberg's calci cation), and it often happens in patients with chronic kidney disease, especially end stage renal disease (ESRD) [1,2]. Lots of studies have demonstrated that vascular calci cation is not a simple passive process of calcium and phosphorus deposition but an active regulatory process, and the transdifferentiation of vascular smooth muscle cells (VSMCs) into osteoblast-like cells is regarded to be the key pathophysiological factor of vascular calci cation [3][4][5]. However, the speci c mechanism of vascular calci cation in patients with ESRD is still not entirely elucidated.…”
Section: Introductionmentioning
confidence: 99%